The effect of providing educational videos on the level of knowledge and attitudes of the Batu City community regarding the use of halal-labeled medicines - Maulina, Novia; Syahrir, Ach; Lestari, Ludy Wiji; Rahmandhani, Farhana Rezi Gita (Science Midwifery, 2024)
Indonesia is the country with the largest Muslim population in the world. For a Muslim, consuming halal products is a necessity and obligation as a form of faith in Allah SWT. However, the awareness of the Muslim community in paying attention to the halalness of medicinal products still needs to be increased. Education regarding halal-labeled medicines is an effort that can be made to increase public knowledge about halal-labeled medicines. Increasing a person's knowledge can form a positive attitude so that public awareness about the importance of halal-labeled medicines can increase. This research aims to find out whether providing educational videos affects the level of knowledge and attitudes of the people of Batu City regarding the use of halal-labeled medicines. This research is a pre-experimental quantitative research with a one-group pretest-posttest design. The research sample was taken using a purposive sampling technique, and the number of research respondents was 100. The results of the research on the normality test showed that the data on the knowledge and attitude variables were not normally distributed, so the Wilcoxon test was carried out, which showed that there were differences in the level of knowledge and attitudes of respondents before and after being given the educational video with a significance value (p-value ˂ 0.05). This research concludes that providing educational videos influences the knowledge and attitudes of the people of Batu City regarding halal-labeled medicines.